2020
DOI: 10.11606/s1518-8787.2020054001774
|View full text |Cite
|
Sign up to set email alerts
|

Bolsa Família program and incomplete childhood vaccination in two Brazilian cohorts

Abstract: OBJECTIVE: To estimate the effect of being a beneficiary of the Bolsa Família Program (BFP) in the vaccination of children aged 13 to 35 months. METHODS: Our study was based on all birth records of residents of Ribeirão Preto (SP) and probabilistic sampling with 1/3 of the births of residents of São Luís (MA), selecting low-income children, born in 2010, belonging to the cohorts Brazilian Ribeirão Preto and São Luís Birth Cohort Studies and eligible for the Bolsa Família program. The information of Cadastro Ún… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
10
0
7
Order By: Relevance
“…This may help to explain why many studies find little-to-no relationship between BF assignment and vaccination compliance. Propensity score studies comparing beneficiary and non-beneficiary children find no compliance differential in surveys from 2005 (Andrade et al, 2012) and 2010 (Silva et al, 2020), consistent with difference-in-differences findings from a 2007 to 2009 panel of verified household medical records (Ford et al, 2020). One study shows BF enrolees in 2009 were more likely to get certain vaccinations on time, but beneficiaries and non-beneficiaries had indistinguishable 98% compliance rates, overall (de Brauw et al, 2012).…”
Section: Inferring Bolsa Família Health Impactsmentioning
confidence: 64%
“…This may help to explain why many studies find little-to-no relationship between BF assignment and vaccination compliance. Propensity score studies comparing beneficiary and non-beneficiary children find no compliance differential in surveys from 2005 (Andrade et al, 2012) and 2010 (Silva et al, 2020), consistent with difference-in-differences findings from a 2007 to 2009 panel of verified household medical records (Ford et al, 2020). One study shows BF enrolees in 2009 were more likely to get certain vaccinations on time, but beneficiaries and non-beneficiaries had indistinguishable 98% compliance rates, overall (de Brauw et al, 2012).…”
Section: Inferring Bolsa Família Health Impactsmentioning
confidence: 64%
“…Séries históricas realizadas em Minas Gerais identificaram tendência decrescente de coberturas para vacinas administradas em menores de dois anos, com destaque para as vacinas pentavalente, VORH, BCG, hepatite A e tríplice viral (13)(14) . Variações regionais nas coberturas vacinais são observadas entre os municípios brasileiros (9,11,(33)(34) e de Minas Gerais (13)(14) . Destaca-se que tais municípios compreendem grandes dimensões territoriais, com destaque equivalente para a desigualdade socioeconômica entre as distintas regiões (9,35) .…”
Section: Discussionunclassified
“…However, the analysis was limited to data from 2005, a year when the enforcing of the CCT conditionalities was still deficient and when low-income regions (eg, North and Northeast Brazil) had barriers of access to primary care coverage 22. A study of children born in 2010, in Ribeirão Preto (Southeast Brazil) and São Luís (Northeast Brazil), concluded that there was no effect of CCT on completeness of the vaccination schedule for children under 2 years of age 24. More recently, a study in the city of Acrelândia (North Brazil) found no difference in the up-to-date vaccination coverage among CCT beneficiary and non-beneficiary children 23.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the PBF, the evidence is also in line with the international scenario. While the study by Rasella et al 8 demonstrated a positive association between the programme’s population coverage and the increase in childhood vaccination coverage against measles, polio and diphtheria, tetanus and pertussis, no associations were found in other studies 21–25. Moreover, there is no evidence about the effect of PBF on timely vaccination.…”
Section: Introductionmentioning
confidence: 95%